MONITORING OF THE ANTI-INFLAMMATORY DRUG PIROXICAM AND THE ANTI-HYPERTENSIVE DRUG ATENOLOL IN AN URBAN STREAM IN TRES LAGOAS, BRAZIL - Pine Americo, Juliana Heloisa [UNESP]; Isique, William Deodato [UNESP]; Perez Ortega, Diego Javier [UNESP]; Sanchez Ortiz, Ivan Andres; Torres, Nadia Hortense; Romanholo Ferreira, Luiz Fernando; Manoel, Leticia de Oliveira; Carvalho, Sergio Luis de [UNESP] (Interciencia, 2015)
Pharmaceuticals production and their consumption by the world population have increased in recent years; as a result, these contaminants have reached the water. In this study, the presence and concentration of the anti-inflammatory drug piroxicarn and the anti-hypertensive and beta-blocker atenolol were evaluated in la Onca stream, Tres Lagoas, MS, Brazil, and the influence of water temperature in the occurrence of these drugs in surface waters was verified. Monitoring of both drugs and water temperature was carried out in the stream for twelve consecutive months. Water samples were taken from six different locations; the target compounds were extracted using solid phase extraction and analyzed by high performance liquid chromatography. To check the influence of water temperature on the occurrence of the pharmaceuticals, a logistic regression model was applied. The drugs were detected in all the points of the stream, the highest concentrations being registered downstream of the wastewater treatment plant. Water temperature inversely proportional influences the occurrence of both drugs in the stream, the higher the temperature of water the lower probability of detection.